Response of Perennial Horticultural Crops to Climate Change - Glenn M; Kim SH; Ramírez Villegas, Julián Armando; Läderach, Peter R.D. (Wiley, 2013)
Perennial horticultural crop production is sensitive to temperature, water availability, solar radiation, air pollution, and CO2. The value of perennial horticultural crops is derived from not only the quantity but also the quality of the harvested product. Perennial crop production is not easily moved as the climatic nature of a region changes due to many socio-economic factors including long reestablishment periods, nearness to processing plants, availability of labor, and accessible markets. Two deciduous temperate fruit crops (apple and grape), two evergreen subtropical crops (citrus and coffee), and two tropical crops (banana/plantain and cacao) were selected as representative case studies. We evaluated the literature affecting the production of these crops to provide an overview of the potential impacts of climate change. The literature survey identified limiting factors and provide information in assessing future climate change impacts. Although lack of data precludes a comprehensive assessment of CO2 responses and interactions with other abiotic (and biotic) factors for most of the crops analyzed, the response of these crops to a doubling of atmospheric CO2 is evaluated. The CO2 fertilization effect may be amplified and sustained longer for perennial horticultural crops if other resources (e.g., nutrients and water availability) are amply supplied, and if proper management options (e.g., spacing, pruning, thinning) are practiced to facilitate the prolonged CO2 effects. This will likely require maintaining intensive and environmentally sustainable cropping systems. In addition, the positive CO2 effect may be negated by the detrimental effects of extreme temperatures on phenology, carbon sinks, reproductive physiology, and changes in the disease/pest complex in the agroecosystem. There is a lack of information on the yield and quality responses of perennial horticultural crops to elevated CO2 and the interaction with warming temperatures. Innovative research, modeling, and field trials for low-input cropping systems that integrate existing knowledge to capitalize on the benefits of elevated CO2, while minimizing the input and costs, and temperature stresses are required to improve understanding in these crop species' responses to climate change and will better address adaptation and mitigation needs in these highly important and complex cropping systems.